AN ICONIC TURN IN PHILOSOPHY - Thaliath, Bahu (Journal of Dharma, 2009)
The term "iconic tum" (Ikonische Wende) was introduced in the 90s in a philosophical discourse by Gottfried Boehm. This phrase appeared for the first time in his treatise "Recurrence of Images" (Wiederkehr der Bilder), written as an introduction to a collection of essays, entitled What Is an Image? (Was ist ein Bildy. This work, particularly the introduction of Boehm, has become in recent years propaedeutic to a discourse which finds resonance not only in the areas of philosophy and art theory, but also in various fields of natural and cultural sciences. The relevance and significance of this discourse has been established mainly through a series of lectures under the theme "Iconic Tum," organized since the winter semester 2001-2002 by the Hubert Burda Foundation at the Ludwig Maximillian University in Munich. The speakers were, apart from renowned art historians like Gottfried Boehm, Willibald Sauerlander; and Martin Kemp, also scholars from other philosophical and scientific disciplines as well as from art, such as Wim Wenders (Film Aesthetics), Alexander Kittler (Media Studies), John Michael Kreis (Philosophy of Cultural Anthropology), Bill Viola (Video Artist), Heinz Otto Peitgen (Mathematics), Jan Assman (Egyptology), Wolf Singer (Neurosciences! Philosophy), Lord Norman Foster (Architecture), and others.